The leadership gap building leadership capacity for competitive advantage - Weiss, David S. (David Solomon) 1953- (John Wiley & Sons Canada, 2005)
Offers the practical, effective strategies you need to close the leadership gap in your organizations, unleashing leadership potential for better business results and a sustainable competitive advantage.